PERANCANGAN APLIKASI PEMANTAUAN KINERJA KARYAWAN BERBASIS ANDROID DI PT. SALESTRADE CORP. INDONESIA - Adi Mardian; Thomas Budiman; Rachmawaty Haroen; Verdi Yasin (Jurnal Manajamen Informatika Jayakarta, 2021)
The challenges facing the organization oriented profit and non profit currently is more complex. PT. Salestrade Corp. Indonesia is a national private company which is engaged in the electrical distributor of various companies in several countries in the world. However, in terms of administration, there is still much that needs to be improve, including in the case of handwritten work reports, attendance has not been recorded properly, there is no control regarding work in the field and there is no system that monitors employee performance. The implementation of this system is not effective and efficient. Therefore, a company needs a computerized system and requires a database to facilitate data storage and access data if needed at any time in order to produce useful information for the company. For that we need an application that functions to monitor employee performance and organize administration and company reports using an Android-based application. With this application it is hopefully that it can help make it easier for companies and employees to make work and attendance reports and make it easier for management to monitor employee performance so that administratively it becomes tidier.